Bystander Empowerment : Sosialisasi dan Strategi Cerdas Menghadapi Verbal Bullying di SMK N 1 Takengon - Mariyani Mariyani; Firmawati Firmawati; Nur Sa’adah; Eliza Sutri Utami; Ardiansyah Ardiansyah; Amrizal Amrizal; Ashari Efendi; Mena Sari; Anisa Mawaddah (BADAN PENERBIT STIEPARI PRESS, 2025)
Bullying is one of the phenomena that often occurs in schools. One type of bullying that occurs is verbal bullying. Several studies have stated that most students still consider the behavior they do to be normal and understandable so that it occurs repeatedly. Therefore, it is important to take quick steps to stop verbal bullying, especially in schools. This study aims to determine the number of students who have experienced verbal bullying, describe the distribution of types of verbal bullying that have been experienced and efforts to prevent verbal bullying. The activity method is community service to students of SMK N 1 Takengon. This service activity is packaged in quantitative form and theoretical activities (lectures) and role playing techniques to describe strategies for dealing with verbal bullying. This activity was carried out during two meetings.